Proposta e avaliação de um modelo computacional de gerador central de padrões - BORGES, Marco Aurélio de Faria (2011)
The concept of Central Pattern Generator-CPG can be described as neural network capable of producing coordinated rhythmic locomotor activity apart from any external rhythm or sensorial stimuli. As this group of neurons are autonomic and are located in the spinal medulla, is experimentally observed that brainless animal‟s exhibit robotized locomotor activity, for its march has no defined direction nor respond to any obstacles. Studies has shown that is possible to activate this specialized networks using specific drugs or electric stimuli depending only of the access area as brainstem, medulla or some brain areas. For this paper many models proposed in current literature were evaluated, in its majority conceptual models. Within this models the Rybak (2006) computational model was chosen to be reproduced and evaluated regarding its robustness. The model in question consist in a CPG based in experimental data collected in cats and it posses two level of neurons based in the half-center models in its structure, the Rhythmic Generator-RG and the Pattern Formation-PF. This groups control the activity of the motoneurons flexors and extensors in an articulation. For its implementation were necessary a simplification in the original model and new parameterization of the variables. The implemented model allows a locomotor activity simulation produced by the CPG when stimulating a Mesencephalic Locomotion Region. Two protocols of variation of conductance inn GR were applied intending to evaluate its strength. The results show that the CPG computer model created operates within physiological values in variations up to . This model presents an adaptation in the first and the current is the current that plays a major role in the occurrence of outbreaks. The conductance has a direct relationship with the period as a result of its increase, a decrease in frequency of the bursts occurs. The conductance of has an inverse relationship with the period and as a result of its increase, a decrease in the period and increased in the frequency of the bursts occurs. The conductance has a direct relation with the period of the bursts before the 100% and a reverse relation after 100% of the reference value. The default behavior extensor/ flexor dominant not only depend on the synaptic weight of RLM, but rather the result of all the conductance values that make up the neuron GR.